(untitled) (Research, Society and Development, 2022)
Objective: To evaluate depressive and anxious signs in elderly people living in a long-stay institution. Methodology: An exploratory, cross-sectional study carried out in Aracaju, Sergipe, with a sample of 25 elderly participants. Three instruments were used for data collection: a questionnaire for sociodemographic characterization, prepared by the researchers themselves; the Abbreviated Geriatric Depression Scale, composed of 15 items of objective answers (yes or no) that sought to assess the feelings of the elderly towards life; in addition to the Beck Anxiety Inventory (BAI), which has a list of common symptoms of anxiety, being answered according to what has been bothering them in the last week, including the day of the research. In the eligibility criteria, the elderly of both sexes and aged 60 years or older were included, excluding the elderly who did not have preserved cognitive capacity, after application of the Mini Mental State Examination. Results: There was a prevalence of females 15 (60.0%), with a mean age of 79.1 years. Of the 25 elderly participants in the study, 15 (60.0%) had mild or severe conditions suggestive of depression. Regarding signs of anxiety, 11 (73.33%) of the women have severe symptoms of the disease, and 4 (26.64%) still have moderate symptoms. With regard to the male elderly, about 7 (70.00%) have severe signs of the disease, and 3 (30.00%) have moderate. Conclusion: It was found that depression and anxiety are present among the elderly living in an institutionalized environment, with an equivalent predominance in both sexes.